We’ll Meet Again: New Classroom Perceptions From Old Material - Milligan, Chris; Cross, Wes (LEARNing Landscapes, 2009)
This article reports on the evolution of a school-based project about Remembrance and World War Two. The focus of the project is the use of wartime era high school yearbooks. The use of digital technology by students to record and analyze prime source archival material, high school annuals, in concert with oral history, and local community study techniques, provides classroom students the opportunity to learn about World War Two from a far more realistic and personal perspective than can be achieved using standard textbooks. It also aids in the development of a greater understanding of the human toll, and a more critical understanding of source material concerning World War Two and other conflicts.